2014
DOI: 10.1111/gcbb.12211
|View full text |Cite
|
Sign up to set email alerts
|

Soil and greenhouse gas responses to biochar additions in a temperate hardwood forest

Abstract: Biochar additions can improve soil fertility and sequester carbon, but biochar effects have been investigated primarily in agricultural systems. Biochar from spruce and maple sawdust feedstocks (with and without inorganic phosphorus in a factorial design) were added to plots in a commercially managed temperate hardwood forest stand in central Ontario, Canada; treatments were applied as a top-dressing immediately prior to fall leaf abscission in September 2011. Forests in this region have acidic, sandy soils, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 60 publications
(105 reference statements)
7
71
2
Order By: Relevance
“…They also tend to be higher in elements such as Ca, Fe, Al and heavy metals, due to factors such as soil contamination of logging waste, mixing of sand or soil in fluidized bed combustion and presumably contact with heated metal surfaces. Three biochar preparations (primarily from softwood; Robertson et al, 2012;Sackett et al, 2015;Criscuoli et al, 2017) had Ca, Mg, P, and S concentrations comparable to our median values, but our K concentrations were much higher (Table 3B). Additional expectation of the composition of wildfire chars may be found by comparison of fresh biomass, and of element recoveries (2015) plus pers comm., Hatton et al (2016), and Pingree et al (2016).…”
Section: Chemistry-other Elementssupporting
confidence: 70%
“…They also tend to be higher in elements such as Ca, Fe, Al and heavy metals, due to factors such as soil contamination of logging waste, mixing of sand or soil in fluidized bed combustion and presumably contact with heated metal surfaces. Three biochar preparations (primarily from softwood; Robertson et al, 2012;Sackett et al, 2015;Criscuoli et al, 2017) had Ca, Mg, P, and S concentrations comparable to our median values, but our K concentrations were much higher (Table 3B). Additional expectation of the composition of wildfire chars may be found by comparison of fresh biomass, and of element recoveries (2015) plus pers comm., Hatton et al (2016), and Pingree et al (2016).…”
Section: Chemistry-other Elementssupporting
confidence: 70%
“…As an organic fertilizer, compost (including SMS) provides plants with important nutrients and facilitates subsequent uptake. Similarly, unweathered BC also provides a short-term pulse of certain important nutrients, in particular K and P [18,62]. If growth responses to BC and SMS treatments are mainly due to nutrient provision, then a saturation of plant nutrient demands will often result in a non-additive positive effect on plant growth (e.g., [63]), and may lead to a decline in plant growth at high levels [28] (p. 46).…”
Section: Discussionmentioning
confidence: 99%
“…), the pyrolysis process (e.g., fast, slow, and gasification), and the temperature during pyrolysis [3,14]. BCs derived from woody feedstock demonstrate particularly important ameliorative properties that include high ability to sorb soil contaminants [15], retain nutrients and water [16][17][18], increase soil pH, and provide pulses of nutrients that are potentially limiting in certain systems (e.g., phosphorus in Pluchon et al [19]). …”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the effects of hardwoodand softwood-derived biochar and P addition on soil microbial community composition and functioning 1 and 2 years after addition in a temperate hardwood forest in Central Ontario. We build upon the work of Sackett et al (2014), who characterized soil properties at this site up to 12 months after biochar addition and found that biochar increased availability of limiting plant nutrients. In addition, Mitchell et al (2015) documented changes in soil microbial flora in a 24-week incubation experiment of these soils, most notably finding an increase in the ratio of bacteria to fungi and a decrease in the ratio of Gram-negative to Gram-positive bacteria with biochar addition.…”
Section: Introductionmentioning
confidence: 99%